Enhancing MSME Competitiveness in Brunei through Halal Certification: Challenges and Training Opportunities - Eva Herianti; Ahmad Yani; Ichwan Arifin; Liza Nora; Amor Marundha; Arna Suryani; Juita Tanjung; Adrian Muluk; Endang Rudiatin; Salahuddin Al Ayubi; Ranisyia dinda alfirani (Universitas Muhammadiyah Jakarta, 2025)
The International Community Service held in Brunei Darussalam occurred at the Embassy of the Republic of Indonesia in Bandar Seri Begawan, targeting Indonesian micro, small, and medium enterprise (MSME) entrepreneurs residing there. This event was organized in collaboration with the Association of Indonesian Accounting Lecturers (ADAI), the Indonesian Community Association, and the Indonesian Muslim Entrepreneurs Association. The main objective was to unify perspectives on addressing pressing halal issues and enhancing MSME competitiveness through halal certification. Featuring knowledge-sharing sessions themed